Box-implanted Nb2O5 nanorods as superior anode materials in lithium ion batteries. Issue 15 (15th October 2017) - Shi, Chongfu; Xiang, Kaixiong; Zhu, Yirong; Zhou, Wei; Chen, Xianhong; Chen, Han
Abstract: One-dimensional Nb2 O5 nanorods were synthesized by hydrothermal method and applied for anode materials in lithium ion batteries. Solid Nb2 O5 nanorods are obtained when surfactant P123 was only utilized in the hydrothermal process, while Nb2 O5 nanorods were pregnant with regular cuboid-shaped boxes when P123 and CTAB surfactants were incorporated. Box-implanted Nb2 O5 (BI-Nb2 O5 ) nanorods exhibit a high reversible capacity of 237.6 mA h g −1 cycled at the current density of 40 mA g −1 after 200 cycles and a remarkable rate capacity of 119.5 mA h g −1 at the current density of 5000 mA g −1 . Their outstanding rate capability can be attributed to regular boxes implanted in Nb2 O5 nanorods, which can provide fast transportation path for lithium ions and electronics and relieve the volume change in charge and discharge process.